(untitled) (European Journal of Health Research, 2015)
Research has shown that polyamines obtained mainly from the diet and digestive tract bacterial source, involved in the development and maturation of intestinal epithelial tropism, both in animals and in infants. Such polyamines may play an important role in the physiology of inflammatory bowel diseases, besides being useful as potential diagnostic marked. Our objectives were to determine the values of biogenic amines in blood and in cultures of enteric bacteria in patients with inflammatory bowel diseases and study their effect on intestinal motility. To do this, we obtained samples of both blood and feces of 20 patients and 31 control cases to process and measure biogenic amines in the HPLC (High Performance Liquid Chromatography). We also did 12 preparations of isolated organs ileum and colon of mice to study intestinal motility. The results show both qualitative and quantitative differences of biogenic amines of blood cells, feces and / or source of enteric bacteria between the control group and intestinal diseases, with different correlations for Crohn’s disease and ulcerative colitis, and between diagnostic markers. The conclusions suggest that the intestinal microbiota in these diseases seems to be different. Furthermore biogenic amines could modulate intestinal motility in both the ileum and colon.